Learning Spreadsheet Tools: The Case of Temperature Dependent Molar Heat Capacity and Change in Molar Enthalpy - Jeremy Lewis (Spreadsheets in Education, 2018)
This paper presents a simple spread sheet tool to calculate a temperature dependent molar heat capacity and change in molar enthalpy from one temperature to another. It assumes a polynomial relationship between temperature and molar heat capacity and tabulates necessary data for seventy compounds. While being a great tool for simple energy balances, the paper provides a detailed step by step account of how the spreadsheet was made using Microsoft Excel®. It pays special attention to features utilized in the creation, including, FREEZE PANE, creating a list from tabulated data, VLOOKUP, IF and AND statements, conditional formatting, and locking cells.